2022
DOI: 10.3390/ani12223093
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strategies to Reduce Equine Strongyle Infective Larvae on Pasture and Study of Larval Migration and Overwintering in a Nordic Climate

Abstract: Horses, as grazing animals, are inadvertently exposed to intestinal parasites that, if not controlled, may cause disease. However, the indiscriminate use of anthelmintic drugs has led to drug resistance, highlighting the need for pasture-management practices to reduce the level of parasitic exposure and lessen reliance on drugs. The efficacy of such methods depends both on the epidemiology of the parasites and the prevailing weather conditions. The aim of the study was to investigate the effect of faecal remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Although the use of anthelmintics has reduced the prevalence of the pathogenic parasite Strongylus vulgaris to low levels, it has also led to the development of anthelmintic resistance in Cyathostominae and Parascaris spp. This highlights the need for a shift towards more sustainable control approaches that limit or prevent the development of resistance ( Osterman-Lind et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the use of anthelmintics has reduced the prevalence of the pathogenic parasite Strongylus vulgaris to low levels, it has also led to the development of anthelmintic resistance in Cyathostominae and Parascaris spp. This highlights the need for a shift towards more sustainable control approaches that limit or prevent the development of resistance ( Osterman-Lind et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To limit the use of anthelmintic drugs, alternatives, such as proper fecal and pasture management methods, should be employed to minimize horse exposure to intestinal parasites ( Osterman-Lind et al, 2022 ). The present study demonstrated that 89.53% of the owners discarded the feces removed from the stalls in the paddock or in the equine living environment, without any other management being carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation